Mean arterial pressure for predicting preeclampsia in Asian women: a longitudinal cohort study - Jun Zhang; Kok Hian Tan; Bernard Chern; Nurul Syaza Razali (BMJ Open)
Objective Previous studies suggested mean arterial pressure (MAP) had moderate predictive values in the first and second trimesters for the prediction of preeclampsia. However, the performance of MAP in Asian women is still unclear. The objective of this study was to examine the predictive values of MAP in Asian population throughout gestation, and to compare the performance of MAP, angiogenic factors and uterine artery Doppler in the prediction of preeclampsia.Design A prospective cohort study.Setting KK Women’s and Children’s Hospital, Singapore.Participants A total of 926 women with singleton pregnancy less than 14 weeks of gestation were included in the prospective Neonatal and Obstetrics Risks Assessment cohort between September 2010 and October 2014. Maternal blood pressure levels, uterine artery pulsatility index (UtA-PI), serum soluble fms-like tyrosine kinase 1 (sFlt-1), placental growth factor (PlGF) and sFlt-1/PlGF ratio were measured at 11–14, 18–22, 28–32 and 34 weeks onward, respectively.Primary and secondary outcomes Preeclampsia was the main pregnancy outcome.Results A total of 20 women developed preeclampsia, who had significantly lower levels of PlGF, higher levels of sFlt-1/PlGF ratio and MAP throughout pregnancy than women without preeclampsia. Compared with angiogenic factors and UtA-PI, MAP had significantly higher area under the receiver operating characteristic curves (AUCs) for predicting preeclampsia and term preeclampsia throughout gestation. For predicting preeclampsia, MAP had AUCs of 0.86 (95% CI 0.78 to 0.95), 0.87 (95% CI 0.80 to 0.95) and 0.91 (95% CI 0.85 to 0.98) at 11–14, 18–22 and 28–32 weeks, respectively. For predicting term preeclampsia, MAP yielded AUCs of 0.87 (95% CI 0.75 to 0.99), 0.87 (95% CI 0.76 to 0.98) and 0.90 (95% CI 0.80 to 0.99) at 11–14, 18–22 and 28–32 weeks, respectively. For predicting preterm preeclampsia, the performance of MAP and PlGF was similar.Conclusion MAP is a good predictor for preeclampsia, especially term preeclampsia, in Asian women.